2022
DOI: 10.1007/s11356-022-22174-x
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metals research in Nigeria: a review of studies and prioritization of research needs

Abstract: Nigeria is experiencing continuous economic and industrial transformations, typical of many developing nations. In addition to its well-established oil industry, which is infamous for exuding various kinds of pollutants, there is increased mining operations, indiscriminate disposal and burning of wastes, illegal oil re nery, and terroristic insurgency, all poised to increase the levels of heavy metal contaminants in the Nigerian environment. A recent revelation indicates that about 2 million people in Southwes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 168 publications
1
8
0
Order By: Relevance
“…These results imply that the Fe content of the soil is very high, thereby obscuring any contributions resulting from release of Fe from the dumped face masks. The observation of high Fe levels in the current study is in agreement with previous studies which had investigated heavy metals concentrations in soil in Nigeria, and had reported higher Fe levels compared to all other metals ( Aiyesanmi et al, 2020 ; Duru et al, 2022 ; Idowu, 2022 ).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…These results imply that the Fe content of the soil is very high, thereby obscuring any contributions resulting from release of Fe from the dumped face masks. The observation of high Fe levels in the current study is in agreement with previous studies which had investigated heavy metals concentrations in soil in Nigeria, and had reported higher Fe levels compared to all other metals ( Aiyesanmi et al, 2020 ; Duru et al, 2022 ; Idowu, 2022 ).…”
Section: Resultssupporting
confidence: 93%
“…This result suggests that a considerable amount of Cu may have ended up in the environment as a result of the huge number of medical face masks used and disposed of during the covid-19 pandemic. Cu has the ability to change between Cu(I) and Cu (II) oxidation states in living systems, causing the generation of hydroxyl and superoxide radicals which are toxic to living tissues ( Stern, 2010 ; Idowu, 2022 ). Although a cofactor for many enzymes, high concentration of Cu destroys bacterial and fungal species in the environment, via lethal interaction of the cupric (Cu 2+ ) state with essential proteins, nucleic acids and metabolites ( Trevors and Cotter, 1990 ).…”
Section: Resultsmentioning
confidence: 99%
“…Once metals have passed through these stages and accumulated in plants, they become available to the local population and herbivores immediately or through the food pyramid. The entry of food pyramid elements is often limited by the movement from the soil to the plant root (Hussain et al, 2021;Vasile et al, 2021;Chen et al, 2022). This crucial step stands heavily influenced by the elements levels in earth orifice mixture that, in turn, are measured by several confined ground properties, including acidity index, water content, humidity, redox potential, and other criteria.…”
Section: Conditions Promoting Bioavailability In Soilmentioning
confidence: 99%
“…Many environmental pollutants, such as toxic metals, are the primary resources of HMs, contaminating water during discharges of industrial and agricultural wastes like pesticides, coal and oil combustion, plastics, and phosphate fertilizers (Munir et al, 2021;Idowu, 2022;Mawari et al, 2022;Mukhi et al, 2022;Borah and Deka, 2023;Xu et al, 2023). The fish accumulated toxic metals from the water via direct water uptake or absorption via the gills, skin, and gut (Marzouk et al, 2016).…”
Section: Fishmentioning
confidence: 99%